The effect of statins on muscle symptoms in primary care: the StatinWISE series of 200 N-of-1 RCTs - Herrett, Emily; Williamson, Elizabeth; Brack, Kieran; Perkins, Alexander; Thayne, Andrew; Shakur-Still, Haleema; Roberts, Ian; Prowse, Danielle; Beaumont, Danielle; Jamal, Zahra; Goldacre, Ben; van Staa, Tjeerd; et al. (Health technology assessment (Winchester, England), 2021)
Uncertainty persists about whether or not statins cause symptomatic muscle adverse effects (e.g. pain, stiffness and weakness) in the absence of severe myositis. To establish the effect of statins on all muscle symptoms, and the effect of statins on muscle symptoms that are perceived to be statin related. A series of 200 double-blinded N-of-1 trials. Participants were recruited from 50 general practices in England and Wales. Patients who were considering discontinuing statin use and those who had discontinued statin use in the last 3 years because of perceived muscle symptoms. Participants were randomised to a sequence of six 2-month treatment periods during which they received 20 mg of atorvastatin daily or a matched placebo. The primary outcome was self-reported muscle symptoms rated using a visual analogue scale on the last week of each treatment period. Secondary outcomes included the participant's belief about the cause of their muscle symptoms, the site of muscle symptoms, how the muscle symptoms affected the participant, any other symptoms they experienced, adherence to medication, the participant's decision about statin treatment following the trial, and whether or not they found their own trial result helpful. A total of 151 out of 200 (75.5%) randomised participants provided one or more visual analogue scale measurements in a placebo period and one or more measurements in a statin period, and were included in the primary analysis. There was no evidence of a difference in muscle symptom scores between statin and placebo periods (mean difference statin minus placebo -0.11, 95% confidence interval -0.36 to 0.14; = 0.398). Withdrawals, adherence and missing data were similar during the statin periods and the placebo periods. Among people who previously reported severe muscle symptoms while taking statins, this series of randomised N-of-1 trials found no overall effect of statins on muscle symptoms compared with the placebo. The slight difference in withdrawals due to muscle symptoms suggests that statins may contribute to symptoms in a small number of patients. The results are generalisable to patients who are considering discontinuing or have already discontinued statins because of muscle symptoms, and who are willing to re-challenge or participate in their own N-of-1 trial. We recommend that additional statins and doses are explored using N-of-1 trials. More broadly, N-of-1 trials present a useful tool for exploring transient symptoms with other medications. This study used 20-mg doses of atorvastatin only. Furthermore, a dropout rate of 43% was observed, but this was accounted for in the power calculations. Current Controlled Trials ISRCTN30952488 and EudraCT 2016-000141-31. This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 25, No. 16. See the NIHR Journals Library website for further project information.